UPAYA MENGHALALKAN PENGGUNAAN PAYLATER MELALUI BAI’ AT-TAQSID DAN MURABAHAH - Afif Sabil (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
The high public interest in using paylater in the market is proof that paylater is an important thing. In the midst of limited costs and very high levels of need, people have chosen paylaters. But on the other hand, paylater falls into the category of usury practices which are prohibited by religion. So, through this qualitative research, a solution is sought that can prevent the use of paylaters from usury practices. The solution in question is to switch to the bai' atitaqshid contract and the murabahah contract.